Effect Combination of Avocado Seed Feed (Persea americana) and Yellow Pumpkin Seed (Cucurbita moschata) on Growth of Nile Tilapia (Oreochromis niloticus) - Nurul Wasilah; Safrida Safrida; Supriatno Supriatno* (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
Feed is the biggest component (50-70%) which causes an increase in production costs, to reduce feed production costs is to mix inexpensive and easily accessible natural feed with a high enough protein content. This study aims to determine the effect of a combination of avocado (Persea americana M.) and pumpkin (Cucurbita moschata D.) seeds on the growth of  nile tilapia (Oreochromis niloticus L.). The design used non-factorial RAL consisted of 4 treatments and 6 replications, namely P0 (control feed), P1 (40 grams of avocado seed feed + 40 grams of pumpkin seeds + 20 grams of mixed material), P2 (20 grams of avocado seed feed + 60 grams of pumpkin seeds + 20 grams of mixed ingredients) and P3 (60 grams of avocado seed feed + 20 grams of pumpkin seeds + 20 grams of mixed ingredients). Data analysis using ANOVA. The results showed that feeding increased the growth of tilapia. In tilapia, a very effective growth was found in P2 feed of 16.44 grams with a growth rate of 3.12% / day. The conclusion of the study indicated that there was an effect of the combination of avocado and pumpkin seeds on the growth of tilapia.